Lepiota sindhudeltana sp. nov. (Agaricaceae; Basidiomycota) from Punjab, Pakistan - Haqnawaz, Muhammad; Rehman Niazi, Abdul; Usman, Muhammad; Nasir Khalid, Abdul (Phytotaxa, 2022)
Lepiota sindhudeltana sp. nov. was found on sandy soil under Saccharum bengalense during fungal surveys to the deltas of the Indus River and the banks of the River Ravi, Punjab, Pakistan. The new species belongs to section Ovisporae, subsection Felininae and is characterized by dull orange appressed squamules on the pileus, thin pileal context, pale yellow lamellae, a stipe rounded to slightly oblong at base, basidiospores broadly ellipsoid to oblong, neither dextrinoid nor amyloid, short, clavate erect pileal hyphae, and narrowly clavate terminal hyphae of the stipitipellis. The closest described species to the new taxon in the phylogenetic tree, based on analysis of ITS and LSU sequences, is L. angusticystidiata. We present the new species with illustrated morphological description, phylogeny, and comparison with related or similar species.